Spirit, Soul, Body : Toward an Integral Christian Spirituality - Consiglio, Cyprian (Book collections on Project MUSE., 2015)
"A perennial problem for spiritual traditions of all sorts is dualism - either a positing of a false distance between the Divine and the created or a rejection of creation and the human body. Many contemporary spiritual seekers have sensed this problem and sought to remedy it through myriad solutions drawn from various spiritual traditions and secular wisdom, both Eastern and Western. Cyprian Consiglio, OSB Cam, explores Christianity's contribution to the discussion. He offers a revisioning and rearticulation of this teaching, based on the prophetic seminal work of Bede Griffiths, toward a practical and integral spirituality that reverences all aspects of our being human - spirit, soul, and body."--